2009
DOI: 10.1007/978-1-4419-1241-1_29
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Optical Pathlength of Human Adult Head at Multi-Wavelengths in Near Infrared Spectroscopy

Abstract: Measurement of multichannel continuous-wave near-infrared spectroscopy (CW-NIRS) is dependent on the modified Beer-Lambert law, which includes optical pathlength (PL) as an essential parameter. PLs are known to differ across different head regions and different individuals, but the distribution of PLs for the whole head has not been evaluated so far. Thus, using time-resolved near-infrared spectroscopy (TR-NIRS), we measured the optical characteristics including PL, scattering coefficients (mu'(s)), and absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…On the basis of these findings, the maximal values of total Hb changes in the left and right auditory channels were subjected to a two-way analysis of variance (ANOVA), with conditions (phoneme and prosody) and sides (left and right) as within-subject factors in each group. It should be noted that Katagiri et al’s (2010) findings do not extend to a comparison across different subjects. Moreover, the two different NIRS systems that differ in the number of lasers used for calculating Hb concentrations (2 vs. 3) were used for the school-age children (ETG-100 for school-age children who stutter and OMM-2001 for school-age children who do not stutter).…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…On the basis of these findings, the maximal values of total Hb changes in the left and right auditory channels were subjected to a two-way analysis of variance (ANOVA), with conditions (phoneme and prosody) and sides (left and right) as within-subject factors in each group. It should be noted that Katagiri et al’s (2010) findings do not extend to a comparison across different subjects. Moreover, the two different NIRS systems that differ in the number of lasers used for calculating Hb concentrations (2 vs. 3) were used for the school-age children (ETG-100 for school-age children who stutter and OMM-2001 for school-age children who do not stutter).…”
Section: Methodsmentioning
confidence: 76%
“…Consequently, the comparison or integration of data between different channels or across subjects may be difficult to justify. However, a recent study demonstrated that the optical path-lengths are similar among nearby channels and between homologous regions of left and right hemispheres within a subject (Katagiri et al, 2010). On the basis of these findings, the maximal values of total Hb changes in the left and right auditory channels were subjected to a two-way analysis of variance (ANOVA), with conditions (phoneme and prosody) and sides (left and right) as within-subject factors in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Note that Hb signals analyzed in the current study do not directly represent cortical Hb concentration changes, but contain an unknown optical path length that cannot be measured. Direct comparison of Hb signals among different channels and regions should be avoided as optical path length is known to vary among cortical regions (Katagiri et al, 2010). Hence, we performed statistical analyses in a channel-wise manner.…”
Section: Methodsmentioning
confidence: 99%
“…Hb signals analyzed in the current study do not directly represent cortical Hb concentration changes, but contain an unknown optical path length that cannot be measured. Since optical path length is known to vary among cortical regions, 68 direct comparison of Hb signals among different channels and regions should be avoided. Therefore, we performed channel-wise statistical analyses.…”
Section: Analysis Of Nirs Datamentioning
confidence: 99%